2020
DOI: 10.1088/2053-1591/ab80a9
|View full text |Cite
|
Sign up to set email alerts
|

Structural relaxation probed by resistance drift in amorphous germanium

Abstract: Amorphous germanium films with different thicknesses are deposited by magnetron sputtering (MS) method. Optical band gap and surface resistance are characterized. Our analysis reveals that there are three kinds of structural relaxation (SR) that may occur in amorphous germanium (a-Ge), and they are spontaneous SR (SSR), annealing-induced SR (AISR), and medium range order (MRO)-tocontinuous random network (CRN) Sr Samples all demonstrate a band gap widening after these kinds of Sr The properties and mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Furthermore, it must be pointed out that the temperature required for the nucleation of a crystallite must not depend on the ion beam fluence. Indeed, whilst the structure of the amorphous phase may vary depending on the fluence, it has been shown that during annealing at such temperatures, the amorphous phase undergoes a structural relaxation towards its lower energy form [28,29]. Hence, at the relatively elevated temperatures used in the present work, the amorphous phase must be in its lower energy form and nucleation of crystallites should occur at the typical crystallization temperature (i.e.…”
Section: Resultsmentioning
confidence: 87%
“…Furthermore, it must be pointed out that the temperature required for the nucleation of a crystallite must not depend on the ion beam fluence. Indeed, whilst the structure of the amorphous phase may vary depending on the fluence, it has been shown that during annealing at such temperatures, the amorphous phase undergoes a structural relaxation towards its lower energy form [28,29]. Hence, at the relatively elevated temperatures used in the present work, the amorphous phase must be in its lower energy form and nucleation of crystallites should occur at the typical crystallization temperature (i.e.…”
Section: Resultsmentioning
confidence: 87%